Late-Onset Ornithine Carbamoyltransferase Deficiency Accompanying Acute Pancreatitis and Hyperammonemia - Marcel Cerqueira Cesar Machado; Gilton Marques Fonseca; José Jukemura (Case Reports in Medicine)
Hyperammonemia related to urea cycle disorders is a rare cause of potentially fatal encephalopathy that is encountered in intensive care units (ICUs). Left undiagnosed, this condition may manifest irreversible neuronal damage. However, timely diagnosis and treatment initiation can be facilitated simply by increased awareness of the ICU staff. Here, we describe a patient with acute severe pancreatitis who developed hyperammonemia and encephalopathy without liver disease. Urea cycle disorder was suspected and hemodialysis was initiated. Following reduction of ammonia levels, subsequent treatment included protein restriction and administration of arginine and sodium benzoate. The patient was discharged to home after 47 days with plasma ammonia within normal range and without neurological symptoms. In clinical care settings, patients with neurological symptoms unexplained by the present illness should be assessed for serum ammonia levels to disclose any urea cycle disorders to initiate timely treatment and improve outcome.